Outer Periarteriolar Lymphoid Sheath Arrest and Subsequent Differentiation of Both Naive and Tolerant Immunoglobulin Transgenic B Cells Is Determined by B Cell Receptor Occupancy - Cook, Matthew C. (The Rockefeller University Press, 1997)
T-dependent B cell responses in the spleen are initiated in the outer periarteriolar lymphoid sheath (PALS) and culminate in the generation of proliferative foci and germinal center reactions. By pulsing anti–hen egg lysozyme (HEL) immunoglobulin transgenic (IgTg) B cells with various concentrations of HEL in vitro before adoptive transfer into normal recipients, it was shown that a critical number of B cell receptors (BCRs) must be ligated for B cells to undergo arrest in the outer PALS. T cell help was manipulated independently of the BCR stimulus by incubating B cells expressing the appropriate major histocompatibility complex class II antigen with a peptide recognized by CD4(+) TCR Tg T cells. B cells which either failed to arrest in the outer PALS due to a subthreshold BCR stimulus, or arrested only transiently due to the brevity of the BCR stimulus, underwent an abortive response within the follicles when provided with T cell help. In contrast, naive B cells stimulated by a sustained, suprathreshold concentration of either foreign or self-antigen and given T cell help, proliferated in the outer PALS and then differentiated. Outer PALS arrest was not influenced by the nature of the B cells occupying the follicle, but appeared to be determined solely by the magnitude of BCR stimulation. Thus antigen-pulsed B cells arrested in the outer PALS in an identical manner irrespective of whether the follicles comprised a population of normal B cells with multiple specificities, a monoclonal naive population, or a monoclonal population of tolerant B cells. In addition, tolerant B cells were found to relocate from the follicles to the outer PALS of HEL/anti-HEL double Tg mice in which the concentration of soluble self-antigen had been increased by zinc feeding. Similarly, when anti-HEL Tg mice were crossed with a second HEL Tg strain expressing a higher concentration of soluble HEL, the tolerant anti-HEL Tg B cells were located constitutively in the outer PALS. Thus, subtle variations in antigen concentration resulted in dramatic changes in positioning of B cells within the spleen. A series of mixed bone marrow chimeras in which the effective antigen concentration was inversely related to the number of self-reactive B cells due to absorption of antigen by transgene-encoded membrane and secreted Ig, was used to confirm that alteration in B cell position previously attributed to changes in follicular composition could be explained on the basis of available antigen concentration, rather than the diversity of the repertoire.